INFLUENCE OF DIGITAL MARKETING STRATEGIES ON CONSUMER BUYING BEHAVIOR IN THE FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA (UNIZIK Journal of Marketing, 2026)
This study examined the influence of digital marketing strategies on consumer behavior among adults in Abuja, FCT, Nigeria. The paper is grounded in the Theory of Planned Behavior and Technology Acceptance Model. A a cross-sectional survey of 384 consumers was conducted across Abuja Municipal Area Council, Gwagwalada, and Kuje using multi-stage stratified sampling from MarchMay 2026. Four strategies were measured: social media marketing, email marketing, search engine marketing, and mobile advertising. Consumer behavior was operationalized as purchase intention, brand loyalty, and electronic word-of-mouth using 5-point Likert scales adapted from validated instruments.
Keywords: Digital Marketing, Email Marketing, Mobile Marketing, Social Media Marketing, Search Engine Marketing, Consumer Buying Behavior